The National Diabetes Prevention Program: From Research to Reality - Albright, Ann (Diabetes Care Educ Newsl, 2012)
The significant rise and projected trends in the incidence of type 2 diabetes argue for a concerted effort on prevention. The strongest currently available evidence for diabetes prevention involves people at high risk for type 2 diabetes (i.e., those with prediabetes). Randomized, controlled trials and translation studies have demonstrated that type 2 diabetes can be prevented or delayed through a structured lifestyle intervention that can be delivered cost-effectively in a variety of settings. For the first time in the United States, a coordinated, focused effort is underway to bring this effective and cost-conscious lifestyle intervention to communities across the country to ultimately reduce the incidence of type 2 diabetes.